Homeostatic regulation of adult hippocampal neurogenesis in aging rats: long-term effects of early exercise - Merkley, Christina M.; Jian, Charles; Mosa, Adam; Tan, Yao-Fang; Wojtowicz, J. Martin (Frontiers in Neuroscience, 2014)
Adult neurogenesis is highly responsive to environmental and physiological factors. The majority of studies to date have examined short-term consequences of enhancing or blocking neurogenesis but long-term changes remain less well understood. Current evidence for age-related declines in neurogenesis warrant further investigation into these long-term changes. In this report we address the hypothesis that early life experience, such as a period of voluntary running in juvenile rats, can alter properties of adult neurogenesis for the remainder of the animal’s life. The results indicate that the number of proliferating and differentiating neuronal precursors is not altered in runners beyond the initial weeks post-running, suggesting homeostatic regulation of these processes. However, the rate of neuronal maturation and survival during a 4 week period after cell division was enhanced up to 11 months of age (the end of the study period). This study is the first to show that a transient period of physical activity at a young age promotes changes in neurogenesis that persist over the long-term, which is important for our understanding of the modulation of neurogenesis by exercise with age. Functional integration of adult-born neurons within the hippocampus that resist homeostatic regulation with aging, rather than the absolute number of adult-born neurons, may be an essential feature of adult neurogenesis that promotes the maintenance of neural plasticity in old age.